STRATEGI PELAKSANAAN PROGRAM PENINGKATAN KESEMPATAN KERJA DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU DAN TENAGA KERJA KABUPATEN KUANTAN SINGINGI - Putri, Imelda; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In the Regency of Singingi, there is a program to increase employement opportunities, which is one program to overcome the number of unemployed people. Through an increase in employment opportunities the community can conduct training and employment skills. The phenomenon that arises in the strategy for implementing job opportunities programs is that the strategy for implementing job opportunities is not maximized, the people who are trained in job training are not in accordance with the desired productivity, there are still many unemployed in Kuantan Singingi Regency. The purpose of this study was to find out the strategy for implementing the job opportunity improvement program in the one stop investment service and Kuantan Singingi Regency. The theoritical concept used in this study is the basic dimension of an organization, reach, and cost control. The selection of informants for this study used purposive sampling technique. The results of study indicate that the strategy for implementing the job opportunity improvement program has not been maximized so that the agency cooperates with private vocational training centers. In addition, there is no scheduling in the implentation of job training. The inhibiting faktors for the program implementation strategy for increasing employment opportunities are the absence of vocational training centers, less than optimal performance, the absence of  optimal information on job vacancies, and budget constraints that cannot accommodate all training costs